POTENSI RIPASUDIL SEBAGAI TERAPI TERBARUKAN UNTUK MENGATASI UVEITIS GLAUCOMA MELALUI INHIBISI RHO KINASE PATHWAY (ROCK) - Ilham Dhiya; Iskandar Purba G; Khartika Mahardini (Journal Medical Universitas muhammadiyah Makassar, 2018)
Uveitis is an inflammatory disease that accounts for 300 thousand new cases of blindness each year in America, and is responsible for 5-10% of vision changes worldwide. First-line therapy for uveitis is topical corticosteroids. Unfortunately, corticosteroid use is a risk factor for glaucoma. About 20-40% of patients experience an increase in pathological intra-ocular pressure that requires secondary glaucoma therapy. To reduce this pressure, the first therapy is beta-blockers and adrenergic agonists. But in inflammatory conditions, therapeutic side effects decrease. Over the years, a new glaucoma therapy agent, Ripasudil, has emerged. Research shows that Ripasudil can not only reduce intraocular pressure in glaucoma, but also has the anti-inflammatory effect needed to treat uveitis. The study of the potential of Ripasudil using literature obtained from the database publications of the journal Pubmed, Clinical Trials and Science Direct. Supporting articles are sought based on specific keywords by the inclusion criteria of articles won in the UK, publications of the past 10 years (except basic science), EBM articles level 1-3 and support the discussion of literature review. Ripasudil can release inflammatory cell infiltration and exudation proteins in aqueous humor. In addition, MCPI-1 protein levels and IL-1, IL-6, TNF-dan, and MCP-1 mRNA levels in the iris-ciliary body decreased after Ripasudil administration. Clinical trials also show that Ripasudil can be used as a glaucoma therapy agent. Ripasudil can be an updated therapy to treat glaucoma uveitis through inhibition of the ROCK pathway and treatment of proinflammatory mediators.